Theoretical and experimental studies on interfacial effects in cellulose nano crystal-shape memory polymer composites - Luo, Hongsheng; Yao, Yangrong; Zhou, Huankai; Wu, Shaoying; Yi, Guobin; He, Xuran; Yang, Jiyuan; Jiang, Yan; Li, Zhengwen (Pigment & resin technology, 2021)
Purpose The purpose of this paper is to study the interfacial effect on mechanical properties of the cellulose nano crystal (CNC)–shape memory polymer (SMP) composites by using combination of the theoretical and experimental approaches. Design/methodology/approach SMP composites were fabricated by introducing CNCs into crystalline shape memory polyurethane. The morphological, thermal and mechanical properties were comprehensively investigated. Theoretical approach based upon the percolation model was used to simulate the storage modulus E’ variation of the composites in crystalline and amorphous states, respectively. The classic two-phase percolation model was used for the amorphous-state composites. Furthermore, a three-phase model consisting of interfacial regions was created for the crystalline-state composites. Findings The deviation of nano fillers mechanical reinforcements was disclosed as the composites triggered thermal transitions. Modified percolation theory involving the interfacial effects greatly enhanced the simulation accuracy. Research limitations/implications The study made the traditional percolating theory suitable for dynamic modulus and polymorphs polymers in terms of mechanics, which may extend the potential application. Originality/value The findings may greatly benefit the development of novel interfacial reinforcing theory and intelligent polymeric nanocomposites featuring polymorphs and dynamic properties.